2020
DOI: 10.1111/ajd.13321
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective review of UVA1 treatment: An Australian experience from a single centre

Abstract: Background: The therapeutic value of ultraviolet A1 (UVA1) phototherapy has been acknowledged for many years. Initially developed predominately for experimental and diagnostic purposes, it was subsequently recognised as a beneficial therapeutic modality in atopic dermatitis and localised scleroderma, and more recently a variety of sclerosing and fibrosing dermatoses, T-lymphocyte mediated disorders, both inflammatory and infiltrative, and several predominately dermal processes previously unresponsive to curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 28 publications
1
24
0
Order By: Relevance
“…In a retrospective review of nine patch GA patients, Aichelburg et al reported four patients to be treated with UVA1 phototherapy, of whom two experienced complete remission while the other two experienced partial remissions [ 83 ]. In another case series of five GA patients treated with UVA1, two experienced complete clearance, two experienced partial clearance, and one patient did not respond to treatment [ 84 ]. In the retrospective study by Nordmann et al, of the 20 patients receiving UVA1 therapy, three experienced full remission, six achieved partial remission, seven had stable disease, and one experienced disease progression [ 59 ].…”
Section: Review Of Management Optionsmentioning
confidence: 99%
“…In a retrospective review of nine patch GA patients, Aichelburg et al reported four patients to be treated with UVA1 phototherapy, of whom two experienced complete remission while the other two experienced partial remissions [ 83 ]. In another case series of five GA patients treated with UVA1, two experienced complete clearance, two experienced partial clearance, and one patient did not respond to treatment [ 84 ]. In the retrospective study by Nordmann et al, of the 20 patients receiving UVA1 therapy, three experienced full remission, six achieved partial remission, seven had stable disease, and one experienced disease progression [ 59 ].…”
Section: Review Of Management Optionsmentioning
confidence: 99%
“…In a contrast to other connective tissue diseases, such as lupus erythematosus and dermatomyositis, SSc does not characterize by increased sensitivity to the sunlight 44 . Phototherapy was almost always well tolerated by SSc patients in reviewed studies, causing only mild‐to‐moderate increased pigmentation or tanning, 16–20,27 skin xerosis, 17,23 transient itch 17,24 and erythema 16,24 . The only case report on the use of oral 8‐MOP in SSc did not identify any difficulties with ingestion of the drug, 16 although its frequent side effect is nausea.…”
Section: Resultsmentioning
confidence: 99%
“…A retrospective evaluation of Pitney et al showed only a partial response in all of four included SSc patients receiving low‐dose (30 J/cm 2 ) UVA1 treatment who experienced improvement of skin elasticity and joint mobility. The authors proposed that such prolonged phototherapy should enhance improvement due to obtaining greater total cumulative dose of UVA1 in the skin 24 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations